Implementing Google Docs Collaboration to Improve Descriptive Writing Skills of Eleventh-Grade Students at SMA Lab School Untad Palu - Syafira Naysilla Putri Atmoko; Sriati Usman; Budi Budi; Darmawan Darmawan (MASI Mandiri Edukasi, 2026)
This research aims to investigate the effectiveness of Google Docs collaboration in improving descriptive text writing skills among eleventh-grade students at SMA Lab School Untad Palu. The research was conducted because many students faced challenges in writing descriptive text, particularly in mechanics (capitalization, punctuation, spelling), organization (logical structure and coherence), and content (idea development and relevance). A quantitative approach with a quasi-experimental pre-test and post-test control group design was employed. The sample consisted of two groups: the experimental group (n = 30), which was taught using Google Docs collaboration, and the control group (n = 29), which received conventional writing instruction. Students' writing skills were assessed using an analytic scoring rubric adapted from Oshima and Hogue (2006), focusing on three components: mechanics (5 points), organization (35 points), and content (20 points), totaling 60 points, converted to a 100-point scale. The descriptive statistics showed that the experimental group achieved notable improvement, with the mean score increasing from 43.67 in the pre-test to 83.43 in the post-test, whereas the control group showed minimal change from 28.48 to 79.31. The Mann-Whitney U test confirmed a significant difference between the groups, indicated by an Asymp. Sig. value of 0.000 < 0.05. These findings demonstrate that Google Docs collaboration helps students provide real-time feedback, revise their work collaboratively, and organize ideas more effectively, resulting in improved writing performance in mechanics, organization, and content. Therefore, Google Docs is considered and effective digital tool for enhancing descriptive writing skills and is recommended for use in English writing classrooms aligned with the Merdeka Curriculum.